Shape and Context-Based Recognition of Standard Mechanical Parts in CAD Models. (February 2023) - Bonino, Brigida; Giannini, Franca; Monti, Marina; Raffaeli, Roberto
Abstract: The work here presented is part of a wider research project aimed at extracting and using in industrial applications high level semantic information from 3D product models that are described by means of their boundary representation (B-rep). The specific focus of the paper is the recognition among the components of the CAD model of an assembly of those belonging to some categories of standard parts largely employed in mechanical industry. The knowledge of these components is crucial to understand the structure of mechanical products as they have specific meaning and function. Standard parts follow international standard in shape and dimensions, and also typical mounting schemes exist concerning their use in the product assembly. These distinctive features have been exploited as a starting point to develop a multi-step recognition algorithm. It includes a shape-based and a context-based analysis both relying on the geometric and topological analysis of a CAD model. As already anticipated by Voelcker in his visionary ability to anticipate open challenges, the shape of an object alone is not enough to understand its function. Therefore, context assessment becomes crucial to validate the recognition given by the shape-based step. It allows to uniquely recognize components in mechanical CAD models, by confirming correct results, refusing the false positives, as well as choosing the correct one when the assignment is multiple. Graphical abstract: Highlights: An approach is shown for semantically enriching CAD models. A two step process for standard parts recognition in CAD models is developed. The recognition is rule-based and exploits engineering knowledge and shape analysis.